Feasibility of brief distress screening for family caregivers of adults diagnosed with schizophrenia in Changsha, Hunan, China. Issue 2 (14th July 2020) - Guan, Ziyao; Cross, Wendy; Lam, Louisa; Wiley, James A.; Sun, Mei; Bai, Xiaoling; Tang, Siyuan
Abstract: What is known on the subject? Distress screening amongst FGs is emphasized in worldwide studies, but existing general tools were found time‐consuming and sometimes inconvenient when using them amongst FGs of patients diagnosed with schizophrenia. The DT, a single‐item scale, was widely used to detect distress amongst FGs of cancer patients, showing good reliability, validity and discrimination power. The 21‐item Depression Anxiety and Stress Scale (DASS21) can identify distress in the general population and serve as a criterion to determine an optimal cut‐off score of the DT. What does the paper add to existing knowledge?: The DT presented good reliability, validity and discriminatory power amongst FGs of adults diagnosed with schizophrenia. A cut‐off score of six maximized sensitivity (77%) and specificity (76%). Over half of the FGs of adults diagnosed with schizophrenia reached this cut‐off score and experienced significant distress. Distress was higher in FGs of male patients, when FGs were parents, and for FGs whose educational background was primary school or below. What are the implications for practice?: The DT is an effective alternative to existing instruments in identifying distressed FGs of adults diagnosed with schizophrenia. It is important to provide FGs with distress screening programmes and interventions (e.g. skill‐building psychoeducation) to identify and relieve distress. In addition, future research could explore brief measures to simultaneously recognize potential negative and positive impacts of caregiving in FGs.